A Study on the Leadership of Female Principals at SMK Negeri 1 Penawar Tama and SMK Negeri 1 Banjar Margo in Tulang Bawang, Lampung - Ari Setioko; Meiliana Bustari (International Journal of Social Sciences, Language, and Education, 2026)
This study examines the leadership practices of female principals at SMK Negeri 1 Penawar Tama and SMK Negeri 1 Banjar Margo in Tulang Bawang, Lampung, using a qualitative multiple case study approach grounded in an interpretive paradigm. Data were collected through semi-structured interviews, observations, and document analysis, involving principals, teachers, and administrative staff. The findings reveal that female principals demonstrate relational, participatory, and adaptive leadership characterized by emotional intelligence, collaborative decision-making, and strategic vision. These practices contribute to the development of a supportive school culture and the enhancement of teacher professionalism. Leadership effectiveness is shaped by multiple factors, including personal attributes, organizational culture, teacher motivation, policy frameworks, and technological demands, indicating that leadership is context-dependent and dynamically constructed. The study also identifies key challenges such as administrative workload, gender-based perceptions, resource limitations, and stakeholder pressures, which influence leadership implementation. Despite these constraints, female principals exhibit resilience and adaptability in navigating institutional complexities. This study contributes to the literature on educational leadership by providing empirical insights from vocational school contexts and underscores the importance of institutional support and gender-responsive policies in optimizing leadership effectiveness.